Development of trofinetide for the treatment of Rett syndrome: from bench to bedside - Kennedy, Melissa; Glass, Larry; Glaze, Daniel G.; Kaminsky, Steve; Percy, Alan K.; Neul, Jeffrey L.; Jones, Nancy E.; Tropea, Daniela; Horrigan, Joseph P.; Nues, Paige; Bishop, Kathie M.; Youakim, James M. (Frontiers in Pharmacology, 2024)
Rett syndrome (RTT) is rare neurodevelopmental disorder caused by mutations in the MECP2 gene that encodes methyl-CpG-binding protein 2 (MeCP2), a DNA-binding protein with roles in epigenetic regulation of gene expression. Functional loss of MeCP2 results in abnormal neuronal maturation and plasticity, characterized by loss of verbal communication and loss of fine and gross motor function, among others. Trofinetide, a synthetic analog of glycine-proline-glutamate, was approved by the US Food and Drug Administration for the treatment of RTT in adult and pediatric patients aged 2 years and older. Here, we present the development of trofinetide from bench research to clinical studies and emphasize how the collaboration between academia, the pharmaceutical industry, and patient advocacy led to the recent approval. The bench-to-bedside development of trofinetide underscores the value of collaboration between these groups in the development and approval of treatments for rare diseases.